Limited doses of immunotherapy use in advanced non‐small cell lung cancer elderly patients with ECOG of 2 and high PDL‐1 expression. Issue 4 (24th October 2021) - Wong, Pui Yee; How, Soon Hin; Hassan, Radhiana; Abdul Azih, Muhammad Naimmuddin
Abstract : Immunotherapy is an effective treatment in advanced non‐small cell lung cancer (NSCLC) patients with high PDL‐1 expression. Here, we report three such patients with durable response despite limited doses immunotherapy.